Pandangan Masyarakat Terhadap Tradisi Larangan Pernikahan Antara Orang Sunda Dengan Jawa - Andriyana, Muhamad Fikri; Masrokhin (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
The aim of this scientific work is to examine the perspective of Islamic law and society regarding the tradition of prohibiting marriage between Sundanese and Javanese people based on the belief that the prohibition emerged. People's views on the problems faced by Sundanese and Javanese couples, as well as "urf" views regarding the existence of prohibitions. This research is a descriptive qualitative study that combines field or empirical studies. A sociological approach is the method used. Three data collection methods were used by the author: interviews, observation, and documentation. The analytical methods used in the analysis are reduction techniques, exposure and drawing conclusions from the data. The overall study concludes that the tradition of prohibiting Sundanese and Javanese marriages has been around for a long time, but is now starting to be abandoned. This tradition also contains myths about impermanence and economic difficulties if the marriage takes place. However, this violates Islamic law, as there is no law against marrying someone from another tribe. This includes things that are prohibited in Islamic marriage, such as mahram, time, and prohibited marriages. According to Ushul Fiqh research, this tradition falls into the category of "urf qauli and fi'li". In their opinion, this tradition is fasid (damaged), because it is contrary to sharia and its rules. As a result, the ban on marriage between Sundanese and Javanese cannot be used as a basis at this time.